Implementasi Perhitungan Biaya Satuan (Unit COST) Berdasarkan Metode Activity Based Costing (ABC) Pada Pelayanan Poliklinik Mata Rumah Sakit X - Novianti, Ariella; Tirta Dharma, Yovita Prabawati; Diyono, Diyono; Andika, I Putu Juni (Innovative: Journal Of Social Science Research, 2025)
Determining appropriate rates is essential to maintaining the financial sustainability of hospitals. The Activity-Based Costing (ABC) method is considered more accurate than traditional methods in calculating the basic rates for ophthalmology polyclinic services, thus assisting management in setting outpatient service rates that align with the resources used for each service. This study aims to compare the service rates of the ophthalmology polyclinic calculated using the ABC method at Hospital X. The research is qualitative with a descriptive case study approach, employing purposive sampling techniques. Data were collected through observations and interviews with the finance and outpatient units and analyzed using thematic qualitative analysis. The results reveal that (1) the ABC method is applied in determining service rates, (2) doctors' service fees are higher than nurses' fees, and (3) rates calculated using the ABC method are lower than those determined using the conventional method employed by Hospital X. In conclusion, the ABC method produces service rates that are lower than the conventional method, indicating that this method is more efficient and accurately reflects resource utilization. Therefore, it can serve as a basis for revising rates to ensure fairness and transparency in hospital services.